1995
DOI: 10.1017/s0022149x00014863
|View full text |Cite
|
Sign up to set email alerts
|

Morphological description of Taenia saginata asiatica (Cyclophyllidea: Taeniidae) from man in Asia

Abstract: In order to clarify the taxonomic status of the Taenia saginata-like tapeworm in East Asia, the morphological characteristics of the adult and cysticercus of classical T. saginata (American, Swiss and Poland strains) and the Taiwan Taenia were compared in the present study. The morphologic characteristics of these two parasites are very similar. The protoscolex of cysticercus of the Taiwan Taenia has a sunken rostellum while that of classical T. saginata has only an apical pit. In addition, the rostellum of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 14 publications
1
39
0
2
Order By: Relevance
“…No further study on the differences of the number of the hooklets and calcareous corpuscles among the various ages of metacestodes had been published. In our study, the rudimentary hooks, that were reported to be inner hooklets by Eom and Rim (1993) and Fan et al (1995), were observed in most but not all of the cysticerci of all the ages. We observed many small-granules aggregates in place of those outer hooklets as reported by Eom and Rim (1993) and Fan et al (1995) in the rostellar region, with few calcareous corpuscles in the 10 week-old cysticerci.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…No further study on the differences of the number of the hooklets and calcareous corpuscles among the various ages of metacestodes had been published. In our study, the rudimentary hooks, that were reported to be inner hooklets by Eom and Rim (1993) and Fan et al (1995), were observed in most but not all of the cysticerci of all the ages. We observed many small-granules aggregates in place of those outer hooklets as reported by Eom and Rim (1993) and Fan et al (1995) in the rostellar region, with few calcareous corpuscles in the 10 week-old cysticerci.…”
Section: Discussionmentioning
confidence: 43%
“…Compared with other human taeniids, the tapeworm of T. s. asiatica has no hook on its rostellum, which differed from T. solium but is similar to the classical T. saginata (Taenia saginata saginata) (Fan et al 1995). However, in the intermediate host, metacestodes of T. s. asiatica parasitize in the viscera (mostly in the liver) of pigs (Fan et al 1995;Eom and Rim 2001), whereas T. s. saginata parasitize in the muscle of cattle (Schmidt and Roberts 2000).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Considerando a maior prevalência de teníase por T. saginata (Dias et al 1991, Esteves et al 2005, bem como a similaridade morfológica entre T. saginata e T. asiatica (Eom & Rim, 1993, Fan et al 1995, que é considerada exótica no país, aliadas à endemicidade de cisticercose humana em muitos estados brasileiros (Machado et al 1988, Agapejev 1996, Takayanagui & Leite 2001, Mendes et al 2005 e às baixas taxas de ocorrência da cisticercose suína (Alves 2000, Flavigna-Guilherme et al 2006), ao contrário do que se observa em bovinos, torna-se imperiosa a necessidade de aprofundar as análises moleculares, com vistas ao esclarecimento de muitos pontos controversos que permanecem no universo cientíϐico, a começar com a possibilidade dos ovos de T. saginata causarem cisticercose no homem, conforme admitiram Santos (1996) e outros autores citados por Pardi et al (2001). Quanto à identiϐicação de C. bovis nos diversos sítios anatômicos estudados, mais uma vez destaca-se a importância de se tornar rotina nos matadouros, os exames de esôfago e ϐígado, pois os resultados encontrados na PCR conϐirmaram o diagnóstico ambulatorial feito nessas localizações.…”
Section: Resultsunclassified
“…A identiϐicação correta dos cisticercos é importante para os estudos epidemiológicos, tendo em vista a descoberta de uma nova tênia, Taenia asiatica , Galán-Puchades & Mas-Coma 1996, que é morfologicamente semelhante a T. saginata (Fan et al 1995), além de espécies em hospedeiros não habituais (Fan et al 1990, Eom et al 1992, Gusso et al 2000, Logt & Gottstein 2000.…”
Section: Introductionunclassified